Prognostic impact of right bundle branch block in hospitalized patients with idiopathic dilated cardiomyopathy: a single-center cohort study. Issue 1 (January 2020) - Lai, Li; Jiang, Rong; Fang, Wei; Yan, Chao; Tang, Yibin; Hua, Wei; Fu, Michael; Li, Xiaoping; Luo, Rong
Objective: Idiopathic dilated cardiomyopathy (IDCM) is a primary myocardial disease resulting in symptoms of heart failure. Right bundle branch block (RBBB) is associated with increased cardiovascular risk and all-cause mortality. Therefore, the present study was performed to identify the prognostic impact of RBBB in patients with IDCM. Methods: In total, 165 hospitalized patients with IDCM were evaluated. Receiver operating characteristic curve analysis was used to determine the cutoff point, and Cox regression was used to assess risk factors. Results: After a median follow-up of 73.1 months (interquartile range, 36.1–88.7 months), 59 (35.8%) patients had died. All-cause mortality was significantly higher in patients with than without RBBB (log-rank χ 2  = 9.400), P<0.05. Significant independent predictors of all-cause mortality in patients with IDCM were RBBB (hazard ratio, 2.898; 95% confidence interval, 1.201–6.995) and the left ventricular end-diastolic dimension (LVEDD) (hazard ratio, 1.034; 95% confidence interval, 1.004–1.066) at admission. Patients with RBBB and an LVEDD of ≥63 mm had the highest mortality (log-rank χ 2  = 14.854), P<0.05. Conclusion: RBBB was an independent predictor of all-cause mortality, and the combination of RBBB and LVEDD provided more clinically relevant information than RBBB alone for assessing the risk of all-cause mortality in patients with IDCM.